Energy poverty vulnerability index: A multidimensional tool to identify hotspots for local action. (November 2019) - Gouveia, João Pedro; Palma, Pedro; Simoes, Sofia G.
Abstract: Energy poverty is a growing societal challenge that puts the welfare of many European citizens at risk. Several different indicators have been developed with the objective of assessing this phenomenon. The aim of this work is to develop a novel high-resolution spatial scale composite index, focusing on space heating and cooling, to map energy poor regions and identify hotspots for local action. The proposed index (EPVI) combines socio-economic indicators of the population (AIAM sub-index) with building's characteristics and energy performance (EPG sub-index). The method was tested for all 3092 civil parishes of Portugal and could be potentially replicated at Pan European scale. Results show a higher prevalence of significative EPVIs in the inland region and the islands, particularly in rural civil parishes. Although cooling EPVIs are generally higher, heating may be a more significant issue in terms of energy demand and health hazard. Energy poverty vulnerability assessment at such a disaggregated regional scale could bridge the gap between common overall country analyses and local-scale initiatives targeting vulnerable households. The outcomes of this paper support national and local energy efficiency policies and instruments while fostering better assessments and enabling local actions for tackling this problem. Highlights: High spatial scale multi-faceted method for EP regional vulnerability assessment. Buildings energy performance gaps and socio-economic variables are combined. Tool for hotspots identification for local action and comparative analysis. Both space heating and cooling problems are highlighted for a Southern EU country.